Effectiveness of a cosmetic device containing a combination of alpha‐ and beta‐hydroxy acids, urea, and thuja for the treatment of seborrheic keratoses. (3rd August 2021) - Campione, Elena; Cosio, Terenzio; Di Prete, Monia; Piccolo, Arianna; Lanna, Caterina; Lombardo, Paolo; Diluvio, Laura; Dika, Emi; Baciorri, Francesca; Orlandi, Augusto; Bianchi, Luca
Abstract: Background: Seborrheic keratosis is a benign epidermal tumor of cosmetic concern—as it progressively increases in size, thickness, and pigmentation—on which topical treatments are poorly effective. Considering its keratotic component, effective products may include active principles with keratolytic action. Aims: Evaluate the efficacy and tolerability of a topical cosmetic product with urea and hydroxy acids, in the treatment of seborrheic keratoses. Patients and Methods: Twenty patients were enrolled in an observational, prospective, open‐label study. The topical device was applied on seborrheic keratoses twice daily for 30 days. We evaluated the progression of the treatment by clinical examination—using Daily Life Quality Index—and epiluminescence microscopy at baseline and day 30. Results: After 30 days of treatment, we documented a significant reduction in seborrheic keratosis thickness and number, which was confirmed also by epiluminescence microscopy. On day 30, global Daily Life Quality Index improved by 99.95%. The tolerability of the cosmetic device was considered excellent, according to 19/20 subjects (95%). Conclusions: The results of our study showed the efficacy and tolerability of this cosmetic device. Its active compounds favor gradual removal of seborrheic keratoses, even in case of pigmented variants. This non‐invasive treatment represents an alternative to surgical procedures, mainly for fragile patients and delicate skin areas. It is possible to speculate its usefulness in the topical treatment of circumscribed hyperkeratosis, palmoplantar keratoderma, and thick psoriatic plaques.